Track‐Etched Magnetic Micropores for Immunomagnetic Isolation of Pathogens. Issue 7 (17th February 2014) - Muluneh, Melaku; Shang, Wu; Issadore, David
<x xml:space="preserve">Abstract</x> A microfluidic chip is developed to selectively isolate magnetically tagged cells from heterogeneous suspensions, the track‐etched magnetic micropore (TEMPO) filter. The TEMPO consists of an ion track‐etched polycarbonate membrane coated with soft magnetic film (Ni20Fe80). In the presence of an applied field, provided by a small external magnet, the filter becomes magnetized and strong magnetic traps are created along the edges of the micropores. In contrast to conventional microfluidics, fluid flows vertically through the porous membrane allowing large flow rates while keeping the capture rate high and the chip compact. By utilizing track‐etching instead of conventional semiconductor fabrication, TEMPOs can be fabricated with microscale pores over large areas A > 1 cm2 at little cost (< 5 C| cm−2). To demonstrate the utility of this platform, a TEMPO with 5 μm pore size is used to selectively and rapidly isolate immunomagnetically targeted Escherichia coli from heterogeneous suspensions, demonstrating enrichment of ζ > 500 at a flow rate of Φ = 5 mL h−1. Furthermore, the large density of micropores (ρ = 106 cm–2) allows the TEMPO to sort E. coli from unprocessed environmental and clinical samples, as the blockage of a few pores does not significantly change the behavior of the device.